Comparative Outcomes of Meropenem–Vaborbactam vs. Ceftazidime–Avibactam Among Adults Hospitalized with an Infectious Syndrome in the US, 2019–2021 - Marya D. Zilberberg; Brian H. Nathanson; Mark A. Redell; Kate Sulham; Andrew F. Shorr (Antibiotics)
Background/Objectives: Meropenem–vaborbactam (MEV) and ceftazidime–avibactam (CZA) are active against “urgent threat” pathogens like carbapenem-resistant Enterobacterales (CRE). However, few studies have compared outcomes between them. Methods: To explore comparative outcomes of MEV vs. CZA, we conducted a multicenter retrospective cohort study of all adult hospitalized patients with a serious infection (sepsis, urinary tract infection [UTI], complicated intraabdominal [cIAI] infection, or pneumonia) within the PINC AI Database, 2019–2021. Descriptive statistics compared the two groups along demographic and clinical characteristics, and multiple regression derived adjusted outcomes. Results: Among 1,989,765 patients who met enrollment criteria, 455 received MEV and 2320 CZA. Compared to CZA, patients on MEV were more commonly Caucasian (68.1% vs. 63.6%, p = 0.032) or Hispanic (21.8% vs. 12.8%, p < 0.001). Their mean [SD] Charlson comorbidity scores did not differ (3.6 [2.5] vs. 3.5 [2.5], p = 0.403). The most common index infection in both groups was pneumonia, though it was less prevalent in the MEV- than the CZA-treated group (48.1% vs. 56.8%, p = 0.001). Fewer than one-third of all patients received the respective drug within 2 days of the onset of the index infection (30.6% MEV vs. 33.0% CZA, p = 0.313). Fewer patients on MEV than CZA required mechanical ventilation (35.0% vs. 41.4%, p = 0.010). MEV treatment was associated with lower adjusted mortality (17.0% [95% CI 13.6%, 20.3%] vs. 20.6% [95% CI 19.0%, 22.2%], p = 0.048) relative to CZA. Conclusions: In this cohort of hospitalized patients treated with either MEV or CZA for their infectious syndrome, MEV was associated with lower adjusted hospital mortality, although the confidence intervals around the values overlapped.